Highly Expressed Soluble Recombinant Anti-GFP VHHs in Escherichia coli via Optimized Signal Peptides, Strains, and Inducers - Chao, Shuangying; Liu, Yuhang; Ding, Ning; Lin, Yue; Wang, Qian; Tan, Junwen; Li, Wei; Zheng, Yang; Hu, Xuejun; Li, Junming (Frontiers in Molecular Biosciences, 2022)
Antigen-binding variable domains of the H chain of heavy-chain antibodies (VHHs), also known as nanobodies (Nbs) are of great interest in imaging technique, disease prevention, diagnosis and therapy. High level expression of soluble Nbs is very important for its industrial production. In this study, we optimized the expression system of anti-GFP VHHs with three different signal peptides (SPs), outer-membrane protein A (OmpA), pectate lyase B (PelB), and L-asparaginase II SP (L-AsPsII) in different E.coli strains via isopropyl β-D-thiogalactoside (IPTG) induction and auto-induction respectively. The solubility of recombinant anti-GFP VHHs with PelB or OmpA was significantly enhanced to the same extent by IPTG induction and auto-induction in BL21(DE3) E.coli strain, and the maximum yield of target protein reached approximately 400 mg/mL in shake-flask. The binding activity of recombinant anti-GFP VHHs was also comfirmed to be retained by native-PAGE. These results suggest that SPs like OmpA and PelB could efficiently improve the recombinant anti-GFP VHHs solubility without changing its bioactivity, providing a novel strategy to optimize the E.coli expression system of soluble VHHs, and laid the foundation for the industrial production of soluble recombinant anti-GFP VHHs and the research of other VHHs in the future.